2007
DOI: 10.1111/j.1556-4029.2007.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between Street Heroin Purity and Drug‐Related Emergencies and/or Drug‐Related Deaths? An Analysis from Vienna, Austria*

Abstract: This study examines the quality of street heroin seized in Vienna in 1999 and whether there was a relationship between the purity of street heroin and the number of heroin-related emergencies as well as the number of heroin-related deaths. Street heroin confiscated by the Viennese police, run-sheets of drug-related emergencies, and postmortem reports of drug-related deaths in Vienna in 1999 were analyzed. A total of 415 retail samples with a total weight of 128.02 g contained a median percentage of 6.5% diacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…However, all the cases used in this study were selected carefully from this specific period in the 1990s (1993–94), and the co-consumption of opioids and stimulant drugs such as cocaine could be excluded, on one hand, for empirical reasons, as stated by Risser et al . 8, and on the other hand could be verified clearly in our study (2.63%). Thirdly, in our study population, pure heroin-related death represented only about a third of the heroin-related deaths: in the other two-thirds, morphine derivatives in combination with another drug and/or alcohol could be detected.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, all the cases used in this study were selected carefully from this specific period in the 1990s (1993–94), and the co-consumption of opioids and stimulant drugs such as cocaine could be excluded, on one hand, for empirical reasons, as stated by Risser et al . 8, and on the other hand could be verified clearly in our study (2.63%). Thirdly, in our study population, pure heroin-related death represented only about a third of the heroin-related deaths: in the other two-thirds, morphine derivatives in combination with another drug and/or alcohol could be detected.…”
Section: Discussionsupporting
confidence: 82%
“…Fourthly, the quality of heroin was not asserted in detail although the codeine detected in about three-quarters of the victims indicate a certain heroin impurity, as already described by Risser et al . 8. However, in an earlier study by Risser et al .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Studies have shown that the purity of illicit heroin might impact on toxicity and increase the risk of an overdose death [3,18]. Moreover, street heroin contains other opiates, such as 6-acetylcodeine, which accounts for the presence of codeine in the blood of heroin users [19].…”
Section: Discussionmentioning
confidence: 99%